STUDI POTENSI INFILTRASI AIRTANAH BEBAS DAERAH MAJALENGKA DENGAN METODA DRASTIC - Hardijana, Dian
Abstract : Study of Groundwater Potential in Majalengka Area's with DRASTIC Methode Qualitative unconfined groundwater infiltration potential analysis based on Drastic method, this method to developed by Lars Rossen for groundwater vulnerability. Drastic method assumed that contaminants flushed into groundwater by precipitation and transported by water to saturated zone, based on the assumption, this method is applicable for groundwater infiltration potential analysis. The case study was carried out in Kabupaten Majalengka. The study shown that, by significance statistical value for seven groundwater parameter, i.e. precipitation, depth to groundwater, land use, hydroulic conductivity, slope of the land surface, and the grain size distribution of geological material's, they have significant correlation with infiltration potential of groundwater. The result of the study in Kabupaten Majalengka area conclude that by Drastic'index range of 23 - 230, Majalengka area can be divide into 5 (five) categories as follow : ? Very potential area with Drastic index 190 - 230 (2.362,13 ha) ? Potential area with Drastic index 149 - 189 (82.028,25 ha) ? Medium potential area with Drastic index 108 - 148 (36.033,62 ha) ? Low potential / No potential area with Drastic index about 67 - 107 ? Very low potential / No potential area with Drastic index about 23 - 66 is critical areas